PELAKSANAAN MEDIASI PENAL SEBAGAI ALTERNATIF DALAM PENYELESAIAN PERKARA TINDAK PIDANA KECELAKAAN LALU LINTAS OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Sindia Dwike Pratika; Evi Deliana; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In general, mediating penalties can be said to be a concept that brings victims and perpetrators together to discuss their interests and willingness to resolve criminal cases, and are assisted by neutral mediators and help resolve criminal cases by providing advice and mediation as mediators. Research on mediation of penalties in traffic accidents by the Pekanbaru City Police Department aims to determine the implementation of penal mediation and the efforts made in its implementation.his type of research can be classified in the type of sociological research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted at the Pekanbaru City Police Department, while the population and sample are all parties related to the problems examined in this study, the data sources used, primary data, secondary data, and tertiary data, data collection techniques in this study with observation and interview.From the results of the study as follows: the implementation of the mediation of the penalties can be carried out in cases of traffic accidents with minor physical injuries, the existence of mutual agreement between the two parties, the existence of a statement not demanding from the victim and the investigator performs a case title for the cases that have been resolved through mediation of the penalties. . While his efforts with the mediation in the Pekanbaru City Police Department traffic accident cases are reduced because it can reduce the number of cases that enter the court. While the obstacles are, among others: a) internal factors, namely: investigators are hesitant to apply penal mediation because there is no paying law and there is no common understanding related to the application of mediation penal; b) external factors, namely: the victim is not willing to be mediated by the penalty, the suspect is not cooperative, and the parties' agreement is not reached.Keywords: Penal Mediation, Traffic Accidents, Minor Injuries, Alternative Case Settlement